Long-term survival in extensive-stage small cell lung cancer: a case report on the integration of interventional bronchoscopy and systemic immunotherapy - Deng, Ganxiu; Yan, Shixuan; Bwembya, Victor; Zhu, Xiaoping; Luo, Zhibing; Deng, Changwen (Frontiers in Oncology, 2026)
Small cell lung cancer (SCLC) is an aggressive malignancy with a poor prognosis, particularly in patients with extensive-stage disease (ES-SCLC). Although the incorporation of immune checkpoint inhibitors (ICIs) into first-line chemotherapy has modestly improved survival, long-term disease control remains rare. Central airway obstruction (CAO), a common complication of advanced SCLC, often leads to respiratory failure and interruption of systemic therapy, further compromising outcomes. We report the case of a 65-year-old man diagnosed with ES-SCLC based on endobronchial ultrasound-guided transbronchial needle aspiration. The patient initially responded to platinum–etoposide chemotherapy but experienced treatment interruption during the COVID-19 pandemic, followed by recurrent malignant airway obstruction and respiratory failure. Repeated bronchoscopic interventions, including tumor debulking, airway stent placement, electrocautery, laser therapy, and cryotherapy, were performed to restore airway patency and stabilize respiratory function, thereby enabling the resumption and continuation of systemic antitumor therapy. Subsequently, chemotherapy combined with the programmed cell death protein-1 (PD-1) inhibitor serplulimab was initiated, followed by maintenance immunotherapy. After local bronchoscopic ablation, transient elevations in circulating inflammatory cytokines, including interleukin-6 and interleukin-8, were observed, suggesting systemic immune activation. The patient achieved sustained partial remission, with preserved airway patency and good general condition. At five years after initial diagnosis, the patient remains alive with stable disease and without severe treatment-related adverse events. This case highlights the potential role of integrating bronchoscopic local interventions with systemic chemotherapy and immunotherapy to enable durable disease control and long-term survival in selected patients with ES-SCLC complicated by central airway obstruction.